Marcello Malpighi: the nervous system under a microscope - ENGELHARDT, Eliasz (Arquivos de Neuro-Psiquiatria, 2021)
The longstanding study of gross anatomy experienced a considerable improvement with the advent of the microscope in the early 17th century. The representative personality of this new era certainly was Marcello Malpighi, seen as “founder of microscopic anatomy”. He studied, with a rudimentary compound microscope, numerous tissues and organs of several classes of animals, as well as plants. He described, for the first time, the microscopic structure of the nervous system, identifying in the gray matter of its various levels minute elements he took as “glands”. It should be reminded that the concept of “cell” (and “nerve cell”) was unknown at his time. Many researchers followed, performing microscopic studies, but without better results, and Malpighi’s view was maintained until the beginning of the 19th century, when new histological processing and staining techniques appeared, as well as improved microscopes.
Keywords: Microscopy; Nervous System; Cerebral Cortex